Kin : thinking with Deborah Bird Rose - Van Dooren, Thom, 1980-; Chrulew, Matthew (Duke University Press, 2022)
"The contributors to Kin draw on the work of anthropologist Deborah Bird Rose (1946-2018), a foundational voice in environmental humanities, to examine the relationships of interdependence and obligation between human and nonhuman lives. Through a close engagement over many decades with the Aboriginal communities of Yarralin and Lingara in northern Australia, Rose's work explored possibilities for entangled forms of social and environmental justice. She sought to bring the insights of her Indigenous teachers into dialogue with the humanities and the natural sciences to describe and passionately advocate for a world of kin grounded in a profound sense of the connectivities and relationships that hold us together. Kin's contributors take up Rose's conceptual frameworks, often pushing academic fields beyond their traditional objects and methods of study. Together, the essays do more than pay tribute to Rose's scholarship; they extend her ideas and underscore her ongoing critical and ethical relevance to a world still enduring and resisting ecocide and genocide. Contributors. The Bawaka Collective, Matthew Chrulew, Colin Dayan, Linda Payi Ford, Donna Haraway, James Hatley, Owain Jones, Stephen Muecke, Kate Rigby, Catriona (Cate) Sandilands, Isabelle Stengers, Anna Tsing, Thom van Dooren, Kate Wright"--